2022
DOI: 10.1177/11207000221128879
|View full text |Cite
|
Sign up to set email alerts
|

Increased hip flexion angle and protrusion of the anterior acetabular component can predict symptomatic iliopsoas impingement after total hip arthroplasty: a retrospective study

Abstract: Background: Iliopsoas impingement (IPI) is a known complication of total hip arthroplasty (THA). The aim of this study was to identify risk factors and the cut-off cup protrusion length for symptomatic IPI. Methods: We retrospectively reviewed 218 hips (46 men, 172 women) of 190 consecutive Japanese patients who underwent primary THA at our institution. Hips with IPI ( n = 24) and control hips ( n = 194) were compared according to age, body mass index, and clinical scores. We evaluated leg-length discrepancy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There are numerous possible causes for iliopsoas tendinopathy following THA, including iliopsoas impingement against a bulging screw or protruding cement. However, the most commonly reported risk factor is cup overhang [4,10,19,34,37,40], with some studies reporting cup overhang, regardless of the amount, to be a risk factor for iliopsoas tendinopathy [4,34,37], while others reported specific thresholds, such as axial cup overhang >12 mm [10,40] and/or sagittal cup overhang >4 mm [40]. This study assessed if cup position influenced posttenotomy clinical scores and found that the improvement in mHHS decreased with increasing sagittal cup overhang at a follow-up ≥ 5 years, with cup overhang measurements having excellent interobserver agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous possible causes for iliopsoas tendinopathy following THA, including iliopsoas impingement against a bulging screw or protruding cement. However, the most commonly reported risk factor is cup overhang [4,10,19,34,37,40], with some studies reporting cup overhang, regardless of the amount, to be a risk factor for iliopsoas tendinopathy [4,34,37], while others reported specific thresholds, such as axial cup overhang >12 mm [10,40] and/or sagittal cup overhang >4 mm [40]. This study assessed if cup position influenced posttenotomy clinical scores and found that the improvement in mHHS decreased with increasing sagittal cup overhang at a follow-up ≥ 5 years, with cup overhang measurements having excellent interobserver agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Iliopsoas impingement against an overhanging cup [13,40], a bulging screw or protruding cement [36] could cause iliopsoas tendinopathy, which is often underdiagnosed when investigating the cause of groin pain [9,11,20]. Recent studies have reported an incidence of symptomatic iliopsoas tendinopathy between 2% and 11% following primary THA [4,23,34,37,40,44].…”
Section: Introductionmentioning
confidence: 99%